Peran Variabel ROE, EPS, dan PBV dalam Penilaian Kinerja Saham Sektor Perbankan di Indonesia: suatu kajian literatur - Yusron, Ahmad (Maliki Interdisciplinary Journal, 2025)
This study is a literature review that discusses in depth the role of fundamental indicators Return on Equity (ROE), Earnings per Share (EPS), and Price to Book Value (PBV) in assessing the performance of banking sector stocks in Indonesia. By referring to various empirical studies conducted in the last five years, this paper evaluates the extent to which each variable has an influence on the movement of bank stock prices listed on the Indonesia Stock Exchange. This study focuses on five selected banking companies, namely BBRI, BMRI, BBNI, BBTN, and ARTO, which represent the categories of large conventional banks to digital banks. The results of the study show that in general, ROE, EPS, and PBV play an important role in investment decisions, although there are differences in results between studies. This study aims to provide insight for investors and academics regarding the effectiveness of the fundamental analysis approach in the context of the Indonesian capital market.